Preparedness for Life-Threatening Situations in a Pediatric Tertiary-Care University Children's Hospital: A Survey - Francis Ulmer; Sabine Pallivathukal; Andreas Bartenstein; Ruth Bieri; Daniela Studer; Sebastiano A. G. Lava (MDPI AG, 2022)
Pediatric nurses and physicians are rarely exposed to life-threatening events. Understanding the needs of clinicians is key for designing continuing training programs. A survey exploring preparedness to manage life-threatening events as well as training needs was mailed to all clinically active nurses and physicians at a tertiary-level referral children's hospital. Overall, 469 participants out of 871 answered the questionnaire (54% response rate). Respondents felt well or very well (nurses 93%, physicians 74%) prepared to recognize a deteriorating child and rated their theoretical understanding (70% well or very well prepared) of how to manage life-threatening situations significantly higher (p < 0.0001) than their cardiopulmonary resuscitation (CPR) preparedness (52% well or very well prepared). Both perceived theoretical understanding (p < 0.0001) and CPR preparedness (p < 0.002) were rated higher among nurses than physicians. Arrhythmias, shock, cardiac arrest and airway management constitute main areas of perceived training need. In conclusion, although a majority of pediatric nurses and physicians felt sufficiently trained to recognize a deteriorating child, their perceived ability to actively manage life-threatening events was inferior to their theoretical understanding of how to resuscitate a child. A high degree of institutional confidence and identification of areas of training need provide a good foundation for customizing future continuing education programs.